2013
DOI: 10.3233/jad-111982
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Consumption Prevents Memory Impairment, Neuronal Damage, and Adenosine A2A Receptors Upregulation in the Hippocampus of a Rat Model of Sporadic Dementia

Abstract: Intracerebroventricular (icv) streptozotocin (STZ) administration induces pathological and behavioral alterations similar to those observed in Alzheimer's disease (AD) and is thus considered an experimental model of sporadic AD. Since caffeine (an adenosine receptor antagonist) and selective antagonists of adenosine A2A receptors modify the course of memory impairment in different amyloid-β-based experimental models of AD, we now tested the impact of caffeine on STZ-induced dementia and associated neurodegener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 64 publications
8
90
0
4
Order By: Relevance
“…This ability of A 2A R KO to prevent A53T α-Syn-induced working memory impairment is consistent with the previous finding that A 2A R blockade prevents memory dysfunction caused by Aβ peptides via p38 MAPK pathway (Canas et al, 2009b;Dall'Igna et al, 2007) and transgenic hAPP AD model (Orr et al, 2015), by R6/2 transgenic model of HD (Li et al, 2015b), by the PD model with focal dopamine depletion in cortex (Kadowaki Horita et al, 2013), and by sporadic dementia (Espinosa et al, 2013). The demonstration of the hippocampal A 2A R up-regulation by A53T α-Syn fibrils and the reversal of α-Syn-induced cognitive impairments suggest a novel molecular mechanism linking α-Syn aggregates to cognitive impairments via the up-regulated A 2A R (in the absence or presence of neurodegeneration).…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…This ability of A 2A R KO to prevent A53T α-Syn-induced working memory impairment is consistent with the previous finding that A 2A R blockade prevents memory dysfunction caused by Aβ peptides via p38 MAPK pathway (Canas et al, 2009b;Dall'Igna et al, 2007) and transgenic hAPP AD model (Orr et al, 2015), by R6/2 transgenic model of HD (Li et al, 2015b), by the PD model with focal dopamine depletion in cortex (Kadowaki Horita et al, 2013), and by sporadic dementia (Espinosa et al, 2013). The demonstration of the hippocampal A 2A R up-regulation by A53T α-Syn fibrils and the reversal of α-Syn-induced cognitive impairments suggest a novel molecular mechanism linking α-Syn aggregates to cognitive impairments via the up-regulated A 2A R (in the absence or presence of neurodegeneration).…”
Section: Accepted Manuscriptsupporting
confidence: 89%
“…Shoham et al (2007) and Espinosa et al (2013) have reported recognition memory impairments in icv-STZ-treated rats, and a comparative study between rodent models of sAD (Chen et al, 2013) has shown that the icv-STZ model is even more detrimental to short-term memory than the transgenic 3xTg-AD mouse model. In line with the icv-STZ impact on cognition, spatial discrimination impairments in STZtreated animals were shown to correlate with reduced choline acetyltransferase (ChAT) activity in the hippocampus (Blokland and Jolles, 1993;Prickaerts et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic dementia is prevented by caffeine administration [26] and the lowest risk of dementia or AD was found among coffee drinkers of 3-5 cups per day at midlife [27], which was attributed to the antioxidant properties of caffeine [28]. The administration of caffeine also prevents the loss of dopaminergic neurons in the substantia nigra [29], which is a feature of PD [30].…”
Section: Caffeine: Potential Beneficial Effectsmentioning
confidence: 99%